1971
DOI: 10.1161/01.str.2.1.81
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Blood Coagulation Following an Acute Stroke

Abstract: Abstract:A Study of Blood Coagulation Following an Acute Stroke• A battery of blood coagulation tests were performed on 14 acute stroke patients. Various abnormalities were found, notably elevation of blood fibrinogen, factor VIII, prothrombin, platelet factor 3, and a shortened P.T.T. The significance of these findings is discussed and they are considered to be of no importance since similar changes were noted in the blood of healthy subjects of the same age range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…This instrument can record continuously and simultaneously fibrin formation of three blood or plasma specimens and provide a permanent record photokymographically." Other studies utilizing thromboelastography for the study of overall coagulation abnormalities are reported by Rosato et al, 8 Sicuteri and co-workers, 4 and Fisch and his colleagues. 5 Kimche and Eisenkraft" had sufficient confidence in the clinical relevance of the TEG data to administer a proteinase inhibitor and low-molecularweight dextran for the treatment of postoperative thromboemboli on the basis of abnormal TEG data, and to utilize daily TEG studies as an index of adequate treatment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This instrument can record continuously and simultaneously fibrin formation of three blood or plasma specimens and provide a permanent record photokymographically." Other studies utilizing thromboelastography for the study of overall coagulation abnormalities are reported by Rosato et al, 8 Sicuteri and co-workers, 4 and Fisch and his colleagues. 5 Kimche and Eisenkraft" had sufficient confidence in the clinical relevance of the TEG data to administer a proteinase inhibitor and low-molecularweight dextran for the treatment of postoperative thromboemboli on the basis of abnormal TEG data, and to utilize daily TEG studies as an index of adequate treatment.…”
Section: Discussionmentioning
confidence: 93%
“…In marked contrast to patients with myocardial infarction where the same authors had previously described an elevated plasma fibrinolytic activity five to eight hours after myocardial infarction, which was depressed 16 to 48 hours following onset of illness, the acute studies of fibrinolytic activity in these stroke patients did not differ significantly from controls. 7 Gaston et al 8 described abnormalities in blood fibrinogen, factor VIII, prothrombin, platelet factor 3, and PTT tests. He felt that these abnormalities were of no clinical significance because similar changes could be noted in the blood of healthy subjects of essentially the same age range.…”
Section: Ettingermentioning
confidence: 99%
“…However, changes in blood coagulation in patients suffering from acute stroke have been described for at least 40 years. Parameters that are well-known, and that confirms this changed coagulation include an activated intrinsic pathway, prothrombin consumption, increased thrombin activity, elevated fibrinogen levels and augmented platelet counts [16,17]. Also, increased thrombin activity on platelet surfaces has directly been attributed to fibrin mesh architecture [18].…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism of anticoagulant treatment in cerebral ischemia is obscure, but perhaps it acts by reducing the "hypercoagulate state" seen in patients with thromboembolic cerebrovascular disease and in elderly persons, 32 and not by stopping the atherosclerotic process.…”
Section: Discussionmentioning
confidence: 99%